2020
DOI: 10.1002/bmc.4929
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of canagliflozin in human plasma samples using a validated HPTLC method and its application to a pharmacokinetic study in rats

Abstract: Canagliflozin (CNZ) is the first sodium-glucose co-transporter-2 inhibitor approved for treatment of type 2 diabetes mellitus. In the proposed work, a sensitive, rapid and validated high-performance thin-layer chromatography (HPTLC) method was established for the estimation of CNZ in human plasma for the first time. HPTLC analysis of CNZ and internal standard (sildenafil) was performed on glass coated silica gel 60 F 254 HPTLC plates using a binary mixture of chloroform-methanol 9:1 (%, v/v) as the mobile phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A review of the literature revealed that different methods were reported for the estimation of GAG either alone (Alam et al, 2020) or in combination with other antidiabetic drugs (Sharif et al, 2020;van der Aart-van der Beek et al, 2020). Also literature review reveals different methods for the simultaneous estimation of CAG and MEF using spectrophotometric (Lotfy et al, 2018;Moussa et al, 2018;Wafaa et al, 2020) and HPLC methods (Gaware et al, 2015;Mohamed et al, 2019;Nalawade et al, 2020;Wattamwar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed that different methods were reported for the estimation of GAG either alone (Alam et al, 2020) or in combination with other antidiabetic drugs (Sharif et al, 2020;van der Aart-van der Beek et al, 2020). Also literature review reveals different methods for the simultaneous estimation of CAG and MEF using spectrophotometric (Lotfy et al, 2018;Moussa et al, 2018;Wafaa et al, 2020) and HPLC methods (Gaware et al, 2015;Mohamed et al, 2019;Nalawade et al, 2020;Wattamwar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The UPLC-MS/MS method was successfully applied to study the influence of telmisartan on the pharmacokinetics and tissue distribution of canagliflozin. This LLE approach was used to process the biological samples due to its higher extraction recovery compared to that of previous LLE approaches and protein precipitation methods (18)(19)(20). Different LLE solvents, including ethyl acetate, dichloromethane, and methyl tert-butyl ether, were explored.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the literature it can be said that very limited techniques are available for simultaneous estimation of Canagliflozin and Metformin HCl in FDC [14][15][16][17][18][19][20][21][22][23][24]. The previous methods are not that much of economic or sensitive so it was thought to develop simple, novel, sensitive and selective method.…”
Section: Fig 1 Chemical Structure Of Canagliflozinmentioning
confidence: 99%